Association of the TNF-a -308G/A polymorphism with lipid profile changes in response to aerobic training program - Leonska-Duniec, A.; Ficek, K.; Switala, K.; Cieszczyk, P. (Biology of Sport, 2019)
Promoter polymorphism of the tumor necrosis factor-a (TNF-a) gene is associated with obesityrelated traits, although the role of its potential modifying effect on changes in obesity-related parameters achieved through a training program is still unknown. The aim of the present study was to examine whether the TNF-a-308G/A polymorphism (rs1800629) influences the effects of a training program. Accordingly, we studied the alleles and genotypes distribution in a group of 168 Polish Caucasian women measured for selected body mass and composition, as well as biochemical parameters before and after the realization of a 12-week aerobic training program. Our results showed that TNF-a genotypes can modulate training-induced biochemical parameter changes such as lipid profile. We demonstrated that carriers of the GG genotype are associated with decreases in post-training high-density lipoprotein cholesterol (HDL-C) levels (p<0.001). Additionally, we revealed that participants with the GG genotype had a higher low-density lipoprotein cholesterol (LDL-C) level (p=0.046) during the entire study period. It could be concluded that harboring the GG genotype of rs1800629 may be considered to be a disadvantageous factor in the context of training-induced effects on lipid profile changes in young female participants.